Potential role of sulphide and ammonia as confounding factors in elutriate toxicity bioassays with early life stages of sea urchins and bivalves. - LOSSO, Chiara; ARIZZI NOVELLI, Alessandra; PICONE, Marco; MARCHETTO, Davide; PANTANI C; GHETTI, Pier Francesco; VOLPI GHIRARDINI, Annamaria (2007)
This work reports some considerations on the possible contribution of sulfide and ammonia to the toxicity of elutriate samples of sediments from the Venice lagoon, tested with a battery of bioassays using early life stages of the sea urchin Paracentrotus lividus and the oyster Crassostrea gigas. A comparison of ammonia or sulfide concentration in the test matrix, matrix toxicity, and the sensitivity limit of bioassays for ammonia or sulfide were used in evaluating toxicity data. Results highlighted that sperm cell and embryo toxicity of elutriates were not affected by sulfides. Neither was any direct relationship shown between elutriate toxicity and ammonia concentration. Most elutriates had ammonia concentrations below the sensitivity limit of acute test methods, while the more sensitive subchronic toxicity tests were affected by ammonia interference in some samples.